Management of Cooperative Learning at SD Magelang 6 - Puryani, Hari (2011)
The objectives of this research are to describe (1) the class setting of cooperative learning at SD Magelang 6; (2) the activity of cooperative learning at SD Magelang 6; (3) the interaction of cooperative learning at SD Magelang 6. It is a qualitative research with ethnography design. This research is conducted at SD Magelang 6. The informants in this research are the principal, teachers, and students. The data collection method uses in-depth interview, observation, and documentation. Data analysis is started with data collection, data reduction, data presentation, and drawing conclusion. The results of the research show that: (1) there are two the class setting of cooperative learning namely classically and group. The group class setting has the difficulty level because needs more time that classical class setting and the teacher should able to create learning condition well to make the learning run effectively. The group class setting facilitate students to discuss, the students trained to use the time effectively, discipline, orderly, and can conditioned themselves; (2) The activity of teacher in cooperative learning conducted before and during the learning process. The teacher analyzes the characteristic of the material, students' ability, time, allocations, tool of infrastructure, teachers' ability, preparing work sheet, and quiz question. In the implementation, the teacher conducts presentation with APM, supervising, and giving quiz. In the discussion, each group has own work system. In giving quiz session, a student given a question by pointing directly and other students can not help; (3) Interaction occurs between the student and teacher and between the student and student. The interaction directed to develop academic capability and social skill includes interpersonal skill, train the cooperation between team members, and individual ability in achieve the goals. The interaction occurred is implemented in skill which is developed by participation, giving question, cooperation, helping friend, active learning, answer question, social attitude, problem solving and so on.